The Effect of Metaphor-based Instruction on Students’ Memory Retention in Islamic Religious Education (IRE) Lectures - Syukri; Rabiatul Adawiyah; Ismail (Jurnal Pendidikan Agama Islam, 2025)
Purpose – The primary objective of the study is to examine the effectiveness of metaphor-based instruction, including the use of teaching props, in enhancing students’ memory retention in Islamic religious education (IRE) lectures. Meanwhile, gender and class differences are treated as comparative variables to explore variations in memory retention across student groups rather than as the main focus of the intervention. The analysis of teaching props functions as a supplementary instructional dimension that strengthens the core metaphor-based strategy. Design/methods/approach – 134 students from five Islamic Religious Education lecture sessions at UIN Mataram participated in this study, which used a quantitative ex-post facto design. A validated 14-item structured memory test comprising metaphor-based instruction, metaphor-assisted teaching props, and student attitude characteristics was used to assess the students' memory recall. Data analysis used descriptive statistics (Rasch model), ANOVA, and post hoc. Findings – The results showed that female students had higher memory than male students. In addition, there were significant differences between classes, with class B showing the highest recall. The aspects of metaphor method and metaphor-assisted teaching aids obtained a percentage of achievement of 89% and 92%, respectively, while the aspect of student attitudes amounted to 69.6%. This study confirms that the metaphor method, especially those assisted by props, is effective in improving student recall in IRE lectures. Research implications/limitations – This research can be an initial reference for Islamic religious education lectures in implementing more varied learning methods. Lecturers also need to train students' attitudes in their teaching. As a result, the students not only   have  knowledge, but also good attitudes like  honesty  and responsibility. Originality/value – The use of the Rasch model and ANOVA test successfully explained the results in detail. The next step is to conduct comparative research on other lecture methods and universities.